Implementasi Kurikulum 2013 Mata Pelajaran Aqidah Akhlak Dalam Membentuk Karakter Siswa Kelas 1a Di Sekolah Dasar Islam Terpadu (Sdit) Muhammadiyah Al-Kautsar Kartasura Kabupaten Sukoharjo Tahun 2015 - Khoirunisa, Nugrahani (2016)
ABSTRACT . Ideals Islamic education is the education that the capable of forming insan kamil, human characterless sublime. Attention the government about character generation began to be considered, bad chacarters to be affecting for our nation future so have to start be improved. Improvement started from a stool in education, education system change begins with evaluation the curriculum has led in to the curriculum refined namely 2013 curriculum. The term character education in indonesia just introduced in 2000, in a united character education not introduced, this finding based on the work of scientific one student in the united. Indonesia for proud of this is because education expert and the community starting to wake up about the importance of character education. The curriculum developed now is 2013 curriculum, the curiculum refined are able to deal with problems the crisis character currently faced by. 2013 curriculum emphasis on education a character having 18 value of a character according to the ministry of national education, among others: religious, honestly, discipline, tolerance, hard work, creative, democratic, curiosity, love of country, independent spirit nationalities, avid reader, appreciate achievement, socially responsible, friendly/communicative, peace-loving, caring environment, responsibility. Password: the implementation of 2013 curriculum, subjects aqidah akhlak, character of students grade 1A.